CONSOLIDATION BEHAVIOUR OF AMORPHOUS PEAT AT KAMPUNG ENDAP, SAMARAHAN, SARAWAK - FELICITY, UMANG JANANG (Universiti Malaysia Sarawak, (UNIMAS), 2018)
Over the past few decades, human population keep on increasing in size resulting in higher demands on high rise structure and infrastructure development. However in Malaysia, it is not always possible to avoid building those developments on peat soil. This is due to large amount of peatland in both Peninsular and Borneo island. Peat is not a preferred soil for any construction due to its high compression and long-term settlement. This Final Year Project discusses on the consolidation behaviour of amorphous peat practically at Kampung Endap, Kota Samarahan. It is crucial to identify different consolidation behaviour of peat because peat is well known for its high compressibility and long-term settlement. By this, the infrastructures built on peat soil will be subjected to sinking due to its consolidation properties. In this study, the physical properties such as moisture content, organic content, liquid and shrinkage limit, and fiber content of amorphous peat in Kampung Endap are determined. Besides that, investigation on the consolidation properties such as compression index, Cc, coefficient of consolidation, Cv, secondary compression index, Cα, and coefficient of volume compressibility, Mv of amorphous peat are conducted and the behaviour of peat subjected to consolidation is analysed and evaluated. Based on the main findings, the consolidation behaviour is governed by the physical properties, soil profiling and environment conditions in which peat is exposed to. Furthermore, a few recommendations are suggested to improve future study.